Electrically pumped lasing from Ge Fabry-Perot resonators on Si - Koerner, Roman; Oehme, Michael; Gollhofer, Martin; Schmid, Marc; Kostecki, Konrad; Bechler, Stefan; Widmann, Daniel; Kasper, Erich; Schulze, Jörg (Optics Express, 2015)
Room temperature lasing from electrically pumped n-type doped Ge edge emitting devices has been observed. The edge emitter is formed by cleaving Si-Ge waveguide heterodiodes, providing optical feedback through a Fabry-Perot resonator. The electroluminescence spectra of the devices showed optical bleaching and intensity gain for wavelengths between 1660 nm and 1700 nm. This fits the theoretically predicted behavior for the ntype Ge material system. With further pulsed electrical injection of 500 kA/cm2 it was possible to reach the lasing threshold for such edge emitters. Different lengths and widths of devices have been investigated in order to maintain best gain-absorption ratios.
CRIS-Team Scopus Importer:2021-06-29